1987
DOI: 10.1116/1.583694
|View full text |Cite
|
Sign up to set email alerts
|

Steps on (001) silicon surfaces

Abstract: We investigate a topological method of eliminating antiphase domains in zinc-blende semiconductors heteroepitaxially grown on (00 1) Si substrates. Antiphase domains cannot occur if only one of the two atomic species of the polar overlayer bonds directly to the substrate at the heteroepitaxial interface (As, in the case of GaAs on Si) and if atoms from only one of the two inequivalent sublattices of the substrate form the termination boundary [only biatomic (a0l2) steps present]. We show that thermal equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 1 publication
1
33
1
Order By: Relevance
“…1, 2, and other measurements where derivative components are observed. The result differs from a previous interpretation [19] of derivative lineshapes in RD spectra in that it is general and not specifically restricted to E 1 transitions. Obviously, the overlap of DY n H r with the surface potential will also influence its lifetime.…”
Section: Applicationcontrasting
confidence: 75%
See 1 more Smart Citation
“…1, 2, and other measurements where derivative components are observed. The result differs from a previous interpretation [19] of derivative lineshapes in RD spectra in that it is general and not specifically restricted to E 1 transitions. Obviously, the overlap of DY n H r with the surface potential will also influence its lifetime.…”
Section: Applicationcontrasting
confidence: 75%
“…Since Bloch waves are infinite in extent, without any mechanism for localizing the final state, properties such as critical point energies and broadening parameters cannot be influenced by effects in a finite surface or interface region. While spatial dispersion can cause measured values of E g to differ from their true bulk values [19], spatial dispersion is not expected to affect excited-state lifetimes and therefore cannot modify G. Thus the presence of derivative components are direct evidence of localization [8]. Using first-order time-dependent perturbation theory and retaining final-state correlations, we have shown that localization follows naturally from the finite penetration depth of photons in spectral regions where materials are optically absorbing [12].…”
Section: Theorymentioning
confidence: 98%
“…Optical anisotropy measurements were performed using an RDS spectrometer that operates at nearnormal incidence from 1.5 to 5.5 eV [21][22][23]. The anisotropy of the complex reflectance r is given by 2( ) ( ) r r r r r r α β α β D / = -/ + , where r α and r β are the complex reflectances of light linearly polarized along the α and β directions, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A method to overcome this problem is the virtual interface ͑VI͒ approach. 31 In this approximation, the optical response of the sample at an appropriate time is converted into that of a virtual substrate material, assuming an ideal surface with no overlayer. Therefore, we did not explicitly consider the formation of the a-BN layer in the initial stage of film growth, and ellipsometric spectra at tϳ2.5 min were used to calculate the optical properties of a VI.…”
Section: Resultsmentioning
confidence: 99%